Efficacy of various synthetic pyrethroid-impregnated encasement materials against house dust mite under laboratory conditions - Sirichit Wongkamchai (2018)
The acaricidal activity of synthetic pyrethroid and benzyl benzoate against Dermatophagoides pteronyssinus was examined in the laboratory, using a specially designed test set up. On the basis of median lethal dose (LD50) values, the compound found to be most toxic to D. pteronyssinus was benzyl benzoate (LD50= 50 mg/m2), followed by permethrin (LD50= 76.7 mg/m2), deltamethrin (LD50= 146.7 mg/m2), esbioallenthrin (LD50= 186.6 mg/m2) and lamdacyhalothrin (LD50= 756.6 mg/m2). Very low toxicity was observed with bifenthrin (LD50= 5157.8 mg/m2). A laboratory control trial was also carried out to compare the acaricidal activity (residual effect) of four pyrethroids impregnated on woven and non-woven encasement materials against house dust mites during a 4-month period. Of the pyrethroids used in this study, esbioallenthrin demonstrated the highest acaricidal activity, and of the pyrethroid impregnated materials, the non-woven encasement material was more effective than the woven encasement material. © Springer 2005.